Mechanism of dislocation channel-induced irradiation assisted stress corrosion crack initiation in austenitic stainless steel. Issue 5 (October 2015) - McMurtrey, M.D.; Cui, B.; Robertson, I.; Farkas, D.; Was, G.S.
Highlights Three classes of dislocation channel–grain boundary intersections were observed. Discontinuous channels undergo the least amount of displacement. Discontinuous channels cause the greatest amount of stress at the grain boundary. Discontinuous channels are the most likely to induce crack initiation. IASCC is due to these high levels of stress at the channel–boundary intersection.